The Effectiveness of Technology-Based Interactive Learning Media to Improve Students' Cognitive Skill at Islamic Elementary School - Sherly Marlita Ariyani; Nurdyansyah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research aims to produce technology-based interactive learning media that is feasible and effective in improving students' cognitive learning process activities. This research uses the Research and Development (RnD) method with the ADDIE research model, namely analysis, design, development, implementation, and evaluation. The research test subjects were fourth-grade students of Darul Hikmah Islamic Elementary School. The data collection techniques used are observation, questionnaires, pre-test, post-test, and documentation. This interactive learning media is validated by material experts, media experts, and linguists if there are deficiencies or expert suggestions, it must be corrected according to the experts' suggestions. The comparative data analysis technique uses SPSS 19 to test the results of the effectiveness test or T-test. The results of interactive learning media development research get a percentage of material validity from material experts of 83%, from media experts getting a percentage of media validity of 80%, and a percentage of language validity of 80% from media experts, interactive learning media is declared feasible and can be tested on grade IV students of Darul Hikmah Islamic Elementary School. Based on the results of the t-test analysis on the pre-test, the average value is 71.40 and the post-test is 81.26. Because of the sig value. (2-tailed) or test 1 of 0.00 which means ≤ 0.05, it can be concluded that Ho is rejected, and Ha is accepted. The conclusion that can be drawn from this study's results shows a significant effect of interactive learning media on the cognitive abilities of fourth-grade students of Darul Hikmah Islamic Elementary School.